2017
DOI: 10.1038/s41467-017-01339-0
|View full text |Cite|
|
Sign up to set email alerts
|

Design rules for light-emitting electrochemical cells delivering bright luminance at 27.5 percent external quantum efficiency

Abstract: The light-emitting electrochemical cell promises cost-efficient, large-area emissive applications, as its characteristic in-situ doping enables use of air-stabile electrodes and a solution-processed single-layer active material. However, mutual exclusion of high efficiency and high brightness has proven a seemingly fundamental problem. Here we present a generic approach that overcomes this critical issue, and report on devices equipped with air-stabile electrodes and outcoupling structure that deliver a record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(174 citation statements)
references
References 54 publications
5
168
1
Order By: Relevance
“…The fact that the physical‐blend device outperformed the host‐only device is not surprising from a radiance and efficiency perspective, since the electroactive compounds of the former feature a higher PLQY (Table ) and since a well‐designed host–guest system is expected to suppress losses from exciton diffusion and doping‐induced self‐absorption . We further speculate that the observed improved turn‐on kinetics of the physical‐blend devices (see Table ) could originate in that the inclusion of the “curved” SBS guest compound into the linear and flat PIDTT host (see Figure b) will “disturb” the ordered PIDTT phase and in the process induce free volume, which allows for a faster redistribution of the bulky ions and improved turn‐on kinetics.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The fact that the physical‐blend device outperformed the host‐only device is not surprising from a radiance and efficiency perspective, since the electroactive compounds of the former feature a higher PLQY (Table ) and since a well‐designed host–guest system is expected to suppress losses from exciton diffusion and doping‐induced self‐absorption . We further speculate that the observed improved turn‐on kinetics of the physical‐blend devices (see Table ) could originate in that the inclusion of the “curved” SBS guest compound into the linear and flat PIDTT host (see Figure b) will “disturb” the ordered PIDTT phase and in the process induce free volume, which allows for a faster redistribution of the bulky ions and improved turn‐on kinetics.…”
Section: Resultsmentioning
confidence: 84%
“…Specifically, the formation of a dynamic p‐n junction doping structure is commonly concomitant with significant quenching of mobile excitons by the LEC‐characteristic high concentration of polarons 5b,9. However, in a recent study it was demonstrated that this polaron‐induced quenching of the exciton can be significantly alleviated in a well‐designed host–guest system, where the majority transport is effectuated by the majority host and the emission is executed by the minority guest. Although several host–guest LECs had been reported previously, this particular study was distinguished by the employment of a for‐this‐purpose designed and selected host–guest system that delivered a strong brightness of >1900 cd m −2 at a record‐high current efficacy of 99 cd A −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemically doped regions, specifically a p‐type doping region at the anode and a n‐type doping region at the cathode, are formed by the redistribution of mobile ions in the active material when a voltage is applied to the device . This electrochemical doping significantly reduces the width of the injection barriers at electrodes, thus allowing for balanced carrier injection, low operating voltage, and high power efficiency from LEC devices comprising a single solution‐processed active layer and air‐stable electrodes …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently the ionic movement decays and the current is mainly driven by electric charge carriers leading the device into a steady state. [53,74] However considering only printed devices the performance is on the same level as other publications or even better especially if taking into account the fully printed concept of our LECs. [45] Here we used a constant current of 12.5 mA cm −2 to investigate the long-term stability of the devices under operation.…”
Section: Wwwadvmattechnoldementioning
confidence: 94%